Status Gizi dan Faktor Lainnya dengan Produktivitas Kerja Tenaga Kerja Pada Masa Pandemi Covid-19 - Sintha Fransiske Simanungkalit; Nanang Nasrulloh; Iin Fatmawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Labor is everyone who can do work to produce goods and services to meet their own needs and for society. Objective: Mencari's relationship between nutritional status, disease history, work motivation, and work discipline with productivity during the Covid-19 pandemic. Method: This type of research uses a cross-sectional research design. The population of this study was the entire non-lecturer workforce, and the sample in this study was 30 people. Results: Uji bivariate obtained a relationship between nutritional status (p= 0.03), work motivation (p = 0.04) with work productivity. Conclusion: A person with a normal nutritional status, good work motivation, and good work discipline can improve labor productivity. Companies are advised to pay attention to the nutritional status of work motivation and discipline.